Jamaican Values and Foreign Policy - Golding, Paul (Technium Social Sciences Journal, 2024)
Dependency theory suggests that the foreign policy of small island developing countries will be congruent to the preferences and interest of larger and more powerful countries in its sphere of influence. A large body of contemporary scholarship asserts that values not only play a role in the mass public’s attitudes toward domestic politics, but that they also help people make sense of attitudes toward international affairs national values, they are influenced by factors such as historical traditions, cultural backgrounds, and the realities of the country. Internal tensions are created when a government pursues a foreign policy that is incongruent with the values of the citizens. This study examined the values of 513 Jamaican citizens using the World Value Survey and discussed these findings within the context of values theory and contemporary foreign policy issues. The secular versus religious divide helps to explain the differences in views on LBGTQ, Abortion and Promiscuity and Abstinence between Jamaica and the hegemon. There is far more congruence in values and culture as it relates to Privacy, Science and Technology, Corruption, and Security. It is important that national culture and values of dependent countries be respected by dominant countries instead of assimilating into one worldview.